Osculating curves and surfaces - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2013)
Osculating circle and osculating sphere have been studied in classical differential geometry [1]. In this article the osculating curves and surfaces of higher order of plane and space curves in Euclidean n-space (n = 2, 3) is considered. We study the intrinsic differential geometry of curves by analyzing their contact with curves and surfaces of higher order.